Management of side effects of antidepressants : brief review of recommendations from guidelines for treatment of major depressive disorder - Uzun, Suzana (Array, 2009)
The side effects of antidepressants are important because they influence treatment process, patients' satisfaction with treatment and adherence to medications. Because of side effects correction of daily dosage of antidepressants is required in some cases, and sometimes therapy with particular antidepressant must be stopped. For this reason, management of side effects of antidepressants is part of routine clinical practice. The objective of this paper is to review recommendations from treatment guidelines and recent articles about management of antidepressants' side effects during treatment of major depressive disorder